Wajah Studi Alquran di Jerman Akhir Abad Ke-20: Terjemahan Alquran Rudi Paret dan Beberapa Pemikirannya - Qadafy, Mu’ammar Zayn (Mutawatir : Jurnal Keilmuan Tafsir Hadith, 2017)
To investigate wriggles of Qurâanic studies at Germany in the end of 20th Century, one should examine works of its influential figure, such as Rudi Paret who was broadly considered as the most intelligent student of Enno Littman, a veteran German orientalist. This article describes and discusses the contribution of Paretâs works along with its methodological strength and fragility based on reviews written by their observers. The results of the passage will be used to map Paret thought, both about Islam and the Qurâan. It is concluded that: first, Paretâs research on the Qurâan contributes a lot to the development of the Qurâanic interpretation methodology; and second, Der Koran: Kommentar und Konkordanz is a work of interpretation based on the translation methodology, in which the text of the Qurâan is understood and explained by something parallel. This method resulted in a âconcordanceâ, Paretâs concrete offer to stand against the chronological reading of the Qurâan that developed rapidly in his days.